RipE expression correlates with high ATP levels in Ehrlichia, which confers resistance during the extracellular stage to facilitate a new cycle of infection - Chien, Rory C.; Lin, Mingqun; Duan, Nan; Denton, Stephen; Kawahara, Jeffrey; Rikihisa, Yasuko (Frontiers in Cellular and Infection Microbiology, 2024)
Ehrlichiosis is a potentially life-threatening disease caused by infection with the obligatory intracellular bacteria Ehrlichia species. Ehrlichia japonica infection of mice provides an animal model of ehrlichiosis as it recapitulates full-spectrum and lethal ehrlichiosis in humans. The E. japonica transposon mutant of EHF0962, which encodes a previously uncharacterized hypothetical protein, is attenuated in both infection and virulence in mice. EHF0962 was hence named here as resistance-inducing protein of Ehrlichia (RipE). Using this ΔripE mutant, we studied how RipE protein contributes to Ehrlichia pathogenesis. Ehrlichia species have an intracellular developmental cycle and a brief extracellular stage to initiate a new cycle of infection. Majority of RipE proteins were expressed on the surface of the smaller infectious dense-core stage of bacteria. Extracellular ΔripE E. japonica contained significantly less adenosine triphosphate (ATP) and lost infectivity more rapidly in culture compared with wild-type (WT) E. japonica. Genetic complementation in the ΔripE mutant or overexpression of ripE in WT E. japonica significantly increased bacterial ATP levels, and RipE-overexpressing E. japonica was more virulent in mice than WT E. japonica. RipE is conserved among Ehrlichia species. Immunization of mice with recombinant RipE induced an in vitro infection-neutralizing antibody, significantly prolonged survival time after a lethal dose of E. japonica challenge, and cross-protected mice from infection by Ehrlichia chaffeensis, the agent of human monocytic ehrlichiosis. Our findings shed light on the extracellular stage of Ehrlichia, highlighting the importance of RipE and ATP levels in Ehrlichia for extracellular resistance and the next cycle of infection. Thus, RipE is a critical Ehrlichia protein for infection as such can be a potential vaccine target for ehrlichiosis.